Selebgram: Meraih Popularitas melalui Cyberspace - sakinah, sakinah - (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2018)
Media communication began to shift toward cyber media with the presence of various kinds of social media as a form of modern communication which not only can share audio information, but also images and video, including Instagram. Uploaded content can be appreciated by netizens who then create public figures in social media instagram, called Selebgram. This article is focused on how netizens categorize selebgram and what selebgrams’ strategies to become popular and how they maintain their popularity. The study shows that netizens categorize a person as a selebgram not only based on the number of followers, the number of likers and comments on the uploaded content, taking endorsement, but also appear in the search field. Some selebgram use fake account provider to get more followers instantly, others beautifying the uploaded content, channelling hobbies, and into coincidental programming. To maintain their followers, a selebgram uploads content by following and creating trends, uploading periodically to update the content of their timeline and utilizing the offered endorsement. It is also found that interaction between selebgram and their followers is more active in Instagram (i.e. comment and direct message) than face to face interaction. Followers even tend to feel reluctant to directly greet, take picture or ask for signature of the selebgram in the view of the fact that selebgram is a celebrity of Instagram, not celebrity in the real world.